The Industrial Action In The New Labor Community Regime - Blancas, Carlos (1980)
The new legislation on labor communities embodied in Decree Laws 21789, Community Industrial, 22329, fishing communities, and 22333, mining communities, has replaced the mechanism of Labor Community participation in the equity ownership of the company, the individual participation of workers in the company's assets by the figure, created by the legislation, of industrial action.